Excess PbI2 Management via Multimode Supramolecular Complex Engineering Enables High‐Performance Perovskite Solar Cells. Issue 35 (28th July 2022) - Zhang, Hengkai; Yu, Wei; Guo, Junxue; Xu, Chao; Ren, Zhiwei; Liu, Kuan; Yang, Guang; Qin, Minchao; Huang, Jiaming; Chen, Zhiliang; Liang, Qiong; Shen, Dong; et al.
Abstract: Excess PbI2 in perovskite film is an effective strategy for boosting perovskite solar cells (PSCs) performance. However, the presence of unreacted PbI2 is a critical source of intrinsic instability in perovskite under illumination, due to the photolysis of PbI2 (decomposed into metallic lead and iodine). Herein, this issue is solved by applying ionic liquids (ILs) on PSCs where the ILs can form types of stable supramolecules with residual lead iodide. The formation process and mechanism of the supramolecules are elucidated. The residual PbI2 is also revealed to cause high level lead interstitial defects and induced tensile strain which further deteriorate device performance. The self‐assembled supramolecular complex can passivate the PSCs where significant enhancements are achieved in both power conversion efficiency (PCE, from 21.9% to 23.4%) and device stability (retaining 95% of the initial PCE after 4080 h in ambient dry‐air storage, and 80% after 1400 h continuous light illumination). Abstract : A stable supramolecular organization modulating strategy is developed to modulate unreacted PbI2 and address both the efficiency and stability issues of perovskite solar cells. The self‐assembled supramolecule is demonstrated to be extremely stable under continuous light illumination in the ambient environment, thus efficiently eliminating the detrimental stability effect of unreacted PbI2 .